(untitled) (Research, Society and Development, 2021)
The HIV/AIDS virus epidemic is considered a phenomenon of large proportions and, due to its pandemic character and severity, represents a major public health problem, lacking more humanized and efficient policies, and in this sense, one of the mos recent methods of prophylaxis to sexual pre-exposure, this is (PrEP) which is an early pharmacological treatment made through the combination of two drugs, which must be taken daily by the user before he has the virus infection. Thus, this article proposes a reflection on the challenges of the offer and effectiveness of PrEP to fight HIV in Brazil. Therefore, a theoretical review of exploratory literature on the subject was carried out using the deductive approach method, with the use of bibliographic data of a qualitative nature through documentary research. From this, it was concluded that through the use of prophylaxis, it was possible to reduce the risk of people acquiring the virus infection, as this strategy proved to be quite effective and safe in people at increased risk of acquiring the infection, however, if makes it important that public policies to fight HIV/AIDS in the country are widely publicized and in order to reach the majority of the public that is vulnerable to contagion by the virus.